(untitled) (Research, Society and Development, 2021)
Introduction: Sleep among medical students has been a factor of discussion in the academic community. Life changes when entering higher education and higher education requirements contribute to losses in the quality of sleep together with a greater incidence of disorders such as Obstructive Sleep Apnea Syndrome. Objective: To evaluate the risk of obstructive sleep apnea syndrome with gender, BMI, and snoring occurrence in third-year medical students at the Universidade Federal de Alfenas. Methodology: The sample consisted of medical students who answered two data collection tools: I) Sociodemographic Questionnaire and II) Berlin Questionnaire. Researchers applied both at the beginning of the third-period course. Results: Higher frequency of snoring among students at high risk for OSAS was observed compared to those at low risk. However, when relating gender and BMI to OSAS, values statistically significant have not been found to classify them as predictive or not predictive factors for the syndrome occurrence. Conclusion: Although significant values for gender and BMI have not been found, the students presented sleep disorders and absolute values of risk occurrence for OSAS. Factors that may affect their academic performance.